2019
DOI: 10.2478/jomb-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 and CARD8 polymorphisms influence risk for asbestos-related diseases

Abstract: Summary Background This study aimed to investigate the association between NLRP3 rs35829419 and CARD8 rs2043211 polymorphisms and the risk of developing pleural plaques, asbestosis, and malignant mesothelioma (MM), and to study the influence of the interactions between polymorphisms and asbestos exposure on the risk of developing these diseases. Methods The case-control study included 416 subjects with pleural plaques, 160 patients with asbestosis, 154 subjects with MM and 149 subjects with no asbestos dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Data on asbestos exposure were available from our previous studies. 30 A standardized questionnaire-based interview was conducted with cases having PP and control group to gather data on their smoking status, whereas data for patients with MM was extracted from medical records at The Institute of Oncology Ljubljana. 31 All participants were fully informed about the purpose of the study and willingly provided their informed written consent to participate.…”
Section: Subjectsmentioning
confidence: 99%
“…Data on asbestos exposure were available from our previous studies. 30 A standardized questionnaire-based interview was conducted with cases having PP and control group to gather data on their smoking status, whereas data for patients with MM was extracted from medical records at The Institute of Oncology Ljubljana. 31 All participants were fully informed about the purpose of the study and willingly provided their informed written consent to participate.…”
Section: Subjectsmentioning
confidence: 99%
“…Beyond these disorders, the role of NLRP3 and its downstream effects through IL‐1 have been implicated in nearly every organ in humans. While some are perhaps more obvious given clear associations with known inflammasome triggers such as in silicosis 167 or asbestosis, 168 others such as neurodegenerative disorders 169 and ovarian aging 153 have been linked to excess NLRP3 activation and expression (Figure 8). For these challenging disorders, inhibitors of NLRP3 have been shown to reduce inflammation in vitro and in vivo, lending new opportunities for intervention.…”
Section: Expanding Role For Nlrp3 In Human Diseasementioning
confidence: 99%
“…Aberrant activation of the NLRP3 inflammasome has garnered significant interest for its potential pathogenic role in inflammatory conditions such as SSc-ILD. Genome-wide association studies have shown polymorphisms in the NLRP3 gene to be linked with the development of ILDs such as asbestosis (rs35829419) ( Franko et al, 2020 ), coal workers pneumoconiosis (rs1539019) ( Ji et al, 2012 ), and silicosis (rs1539019 and rs34298354) ( Weng et al, 2015 ); while specific NLRP3 polymorphisms have yet to be identified in SSc-ILD, further study in this arena could identify convergent molecular mechanisms linking divergent disease states. However, translational work completed by Artlett and colleagues demonstrated the connection between NLRP3 inflammasome activation and SSc by showing that dermal fibroblasts from SSc patients exhibit increased expression of inflammasome components, and that experimentally induced caspase-1 inhibition of both dermal and lung SSc fibroblasts ameliorated collagen deposition, reduced IL-1β and IL-18 secretion, and decreased αSMA (alpha smooth muscle actin) expression ( Artlett et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%